Analysis of Management Information System Design in Pre-Recruitment HR Planning Based on Flowchart - Priyo Yulianto; Lilia Pasca Riani (Universitas Nusantara PGRI Kediri, 2025)
Research aim : This study aims to design and develop an effective management information system to support the pre-recruitment planning process in Human Resources (HR) management using a flowchart-based approach. Design/Method/Approach : This study uses the Research and Development (R&D) method with the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. Data were collected through interviews and literature studies to identify needs and challenges in pre-recruitment HR planning . Research Findings : The results of the study indicate that the developed system can integrate candidate data management, job analysis, and job description preparation systematically. The use of flowcharts as a visualization tool improves understanding and efficiency in the pre-recruitment HR planning process. Theoretical contribution/Originality : This study contributes to the literature on management information systems by emphasizing the importance of information technology integration in the pre-recruitment HR planning process, as well as demonstrating how flowcharts can be used to visualize HR planning workflows . Practitionel/Policy implications: This research provides practical guidance for organizations to improve efficiency and accuracy in candidate data management and formulate more effective and transparent recruitment strategies. Research limitations: This research focuses on system design and does not include the direct implementation stage, so the results need to be tested further in real practice.